ASSESSMENT OF MICROBIAL POLLUTANTS INSIDE LIVESTOCK SHEDS IN AN ORGANISED FARM - D. Divyalakshmi; N. Kumaravelu; B. Samuel Masilamoni Ronald; S. Meenakshi Sundaram (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Intensive livestock production is a significant source of microbial air contamination which affects human and animal health. The present study was conducted to assess microbial pollutants inside livestock sheds in an organised farm. Air samples inside dairy, pig fattener sty and farrowing pens were collected using air sampler to identify Total Bacterial count, Mould count and Coliform count. Total Bacterial Count (CFU/m3) was found to be minimum in dairy sheds during summer (152.49±12.92) and maximum in farrowing pen during rainy season (382.33±38.83). Mould count (CFU/m3) ranged between 48.75±7.78 and 235.00±20.73 between seasons in livestock sheds. Coliform count (CFU/m3) was minimum in dairy shed during rainy seasons (11.25±5.09) and maximum in winter seasons in farrowing pens (31.25 ±7.96). Bacterial isolates such as Staphylococcus epidermidis, Salmonella, Edwardsiella sp, Flavobacterium sp, Micrococcus sp, Pasteurella sp, Mannheimia sp, E.coli, Klebsiella sp, Bordetella sp, Enterobacter sp,   Aeromonas sp, Bacillus sp, Proteus sp, Actinomyces sp, Cornybacterium sp, Pseudomonas sp  from the floor of livestock sheds were isolated and identified.